The Wiley Blackwell handbook of the psychology of recruitment, selection and employee retention - Goldstein, Harold, 1965-; Pulakos, Elaine Diane; Passmore, Jonathan; Semedo, Carla, 1973- (Chichester, West Sussex : Wiley Blackwell, 2017)
This handbook makes a unique contribution to the fields of organizational psychology and human resource management by providing comprehensive coverage of the contemporary field of employee recruitment, selection and retention. It provides critical reviews of key topics such as job analysis, technology and social media in recruitment, diversity, assessment methods and talent management, drawing on the work of leading thinkers including Melinda Blackman, Nancy Tippins, Adrian Furnham and Binna Kandola. The contributors are drawn from diverse backgrounds and a wide range of countries, giving the volume a truly international feel and perspective. Together, they share important new work which is being undertaken around the globe but is not always easily accessible to real-world practitioners and students.
The psychology of employee recruitment, selection, and retention / Harold W. Goldstein, Elaine Pulakos, Jonathan Passmore and Carla Semedo -- The contribution of job analysis to recruitment / James A. Breaugh -- Global recruiting / Jean M. Phillips and Stanley M. Gully -- Applicant reactions to hiring procedures / Donald M. Truxillo, Talya N. Bauer and Alexa M. Garcia -- Applicant attraction to organizations and job choice / Adrian Furnham and Kat Palaiou -- Ethics in recruitment and selection / Nuno Rebelo dos Santos, Leonor Pais, Carla Cabo-Leit?o and Jonathan Passmore -- Using ability tests in selection / Jes{u3806}. Salgado -- Using personality questionnaires for selection / David J. Hughes and Mark Batey -- Using interviewing in selection / Melinda Blackman -- The contribution of others methods in recruitment and selection : biodata, references, resumes, cvs / Adrian Furnham -- Situational judgment tests for selection / Jan Corstjens, Filip Lievens and Stefan Krumm -- The role of simulation exercises in selection / Ryan S. O?Leary, Jacob W. Forsman and Joshua A. Isaacson -- The potential of online selection / Dave Bartram and Nancy Tippins -- Gamification, serious games and personnel selection / Michael Fetzer, Jennifer McNamara and Jennifer L. Geimer -- Team assessment and selection / Mengqiao Liu, Jason L. Huang, and Marcus W. Dickson -- Selection for virtual teams / Geeta D'Souza, Matthew S. Prewett and Stephen M. Colarelli -- Assessment for leader development / Neta Moye, Rose Mueller-Hanson and Claus Langfred -- Talent management in a gender diverse workforce / Jeanette N. Cleveland, Jaclyn Melendez and Lauren Wallace -- Race and cultural differences on predictors commonly used in employee selection and assessment / Charles A. Scherbaum, Michael M. DeNunzio, Justina Oliveira and Mary Ignagni -- Legal and fairness considerations in employee selection / Kenneth P. Yusko, Brian L. Bellenger, Elliott C. Larson, Paul J. Hanges and Juliet R. Aiken -- Employee turnover and strategies for retention / Angela R. Grotto, Patrick K. Hyland, Anthony W. Caputo and Carla Semedo -- Talent management and retention / Crystal Zhang and Jim Stewart -- The impact of organizational climate and culture on employee turnover -- Mark g. ehrhart and maribeth kuenzi -- The impact of work-life balance on employee retention / Kristen M. Shockley, Christine R. Smith and Eric Knudsen -- Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 23, 2017).
Keywords: Employee selection; Employee retention; Psychology, Industrial; Electronic books